Volume II: Thermal Behaviour, Energy Efficiency in Buildings and Sustainable Construction - Santos, Paulo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This second volume of the Special Issue includes 13 contributions, from across the world, with very interesting research topics such as: Energy Intensity Reduction; Large-Scale Non-Residential Buildings; Dynamic Control of HVAC with Heat Pumps; Reed Potential as a Regenerative Building Material and Their Performance Characterisation; Experimental Evaluation of Energy-Efficiency in a Holistically Designed Building; A Case Study of Design and Energy Performance Analysis of a Hotel Building in a Hot and Dry Climate; Internal Convective and Radiative Heat Transfer Coefficients for a Vertical Wall in a Residential Building; Passive Façade Performance Evaluation with Shape Memory Alloy (SMA) during the Architectural Design Process; Thermal Performance Improvement of Double-Pane Lightweight Steel Framed (LSF) Walls Using Thermal Break Strips (TBS) and Reflective Foils; Energy Performance of Buildings with Thermochromic Windows in Mediterranean Climates; Energy Performance and Benchmarking for University Classrooms in Hot and Humid Climates; Effect of HVAC's Management on Indoor Thermo-Hygrometric Comfort and Energy Balance: In Situ Assessments on a Real nearly Zero Energy Building (nZEB); Stochastic-Based Optimisation Approach towards the Integration of Photovoltaic Panels in Multi-Residential Social Housing; Effect of Climate Change and Occupant Behaviour on the Environmental Impact of the Heating/Cooling Systems of a Real Apartment: A Parametric Study through Life Cycle Assessment; Road Thermal Collector for Building Heating in South Europe (Italy): Numerical Modeling and Design of an Experimental Set-Up.